Kommunal melkeku, regional kraftfilial eller lokalt lokomotiv? - Yngve Nilsen (Heimen)
Abstract The article examines different possible paths for the regional and municipality-owned power company BKK following the Norwegian energy liberalisation in 1990, as these paths were promoted by different stakeholders. The state power company Statkraft wanted BKK as a dependent subsidiary, the local political majority wanted it as a source of shareholder value and the company’s employees wanted it as a local provider of jobs. After a period of tug of war, BKK’s regional embeddedness was preserved.